Taking the Spirit Out of Levelling - Abdullah, Khairul Anuar (Fakulti Ukur dan Harta Tanah, 1994)
Orthometric heights are normally derived using conventional spirit levelling techniques. Such techniques have always been one of the more laborious, timeconsuming and costly exercises in surveying. However, with the advent of GPS, ellipsoidal heights can be derived very accurately over a short period.Thus, for many applications, the GPS technique can replace the spirit level method in determining Orthometric height. This is accomplished by converting the GPS derived ellipsoidal height into Orthometric height. This paper describes three method that can be employed for such conversion process. They comprise of a local geoid surface fitting solution, a local gravimetric solution and a global geoid solution. A test network located in the north-east of England was used in this study.